Examining the consequences of customer-oriented deviance in retail. (January 2021) - Mortimer, Gary; Fazal-e-Hasan, Syed Muhammad; Strebel, Judi
Abstract: Retail employees sometimes breach company rules and policies in order to assist their customers. Referred to as customer-oriented deviance (COD), the phenomenon is defined as intentional behaviours that depart from the norms of a referent group in honorable ways. While researchers have begun to examine the important organisational contributions that positive deviance delivers, there have been calls to develop a better understanding of the direct and indirect consequences of such behaviours. Accordingly, conceptual model was tested on a sample of 390 frontline service employees, elucidating the complex relationships between COD behaviours, self-perceptions of service quality and organisational commitment intentions. The current research also examines the moderating effect of gender on these complex relationships. The model offers a strong psychological explanation of how an employee's COD behaviours impact on their self-perception of their service reliability, responsiveness, assurance and empathy, which leads to greater overall commitment to the organisation. This research also finds an employee's gender moderates several of these relationships. The work offers practitioners insight into the important role of employee empowerment in service organisations. The research calls for further empirical examinations of COD behaviours, including antecedents and the mediating roles of perceived risk and tenure.